Systolic and diastolic dysfunction in cirrhosis: a tissue‐Doppler and speckle tracking echocardiography study. (25th April 2013) - Sampaio, Francisco; Pimenta, Joana; Bettencourt, Nuno; Fontes‐Carvalho, Ricardo; Silva, Ana P.; Valente, João; Bettencourt, Paulo; Fraga, José; Gama, Vasco
Abstract Background & Aims Cardiac dysfunction has been described in patients with cirrhosis. Conventional echocardiographic methods are frequently unable to detect abnormalities at rest and have limitations. We aimed to evaluate cardiac function in cirrhosis patients assessing: (i) left ventricular systolic function using speckle‐tracking imaging; (ii) diastolic function using a tissue‐Doppler based algorithm and comparing it with previously proposed definition of diastolic dysfunction (DD). Methods We included 109 hospitalized and ambulatory patients with cirrhosis and 18 healthy controls. Detailed echocardiographic evaluation was performed including tissue‐Doppler and speckle‐tracking analysis. Results Peak systolic longitudinal strain (PLS) was lower in patients [−19.99% (−21.88 to −18.71) vs −22.02% (−23.10 to −21.18), P = 0.003]. Ejection fraction was similar in patients and controls [64% (59–67) vs 61% (60–65), P = 0.42)]. Based on mitral‐flow pattern, DD was present in 44 patients (40.4%). Patients without DD had higher cardiac output compared with those with DD [6.4 L/min (5.4–7.2) vs 5.6 L/min (4.6–6.8), P = 0.02]. Using a tissue‐Doppler based definition, the prevalence of DD was 16.5%. No differences in haemodynamic variables were found in patients with and without this definition of DD. The agreement between the two definitions of DD was weak (kappa = 0.24, P = 0.003). Echocardiographic abnormalities in systolic and diastolic function were not different in compensated vs decompensated patients in different Child‐Pugh classes or cirrhosis aetiologies. Conclusions Patients with cirrhosis have systolic and diastolic cardiac dysfunction at rest. Newer echocardiographic techniques may identify patients with functional impairment more accurately than conventional methods, which are more influenced by flow conditions.